Single molecule tracking studies of solvent-swollen microdomains in cylinder-forming polystyrene-Poly (ethylene oxide) diblock copolymer films - Sapkota, Dol Raj (Kansas State University, 2016)
Solvent swelling of block copolymer microdomains plays an essential role in the improvement of microdomain alignment by solvent vapor annealing and in chemical separations using block copolymer monoliths. Here, investigation of the effects of solvent swelling on the molecular permeability and dimensions of cylindrical microdomains in polystyrene-block-poly(ethylene oxide) (PS-b-PEO) films is done by using single molecule tracking. These films are prepared by sandwiching benzene (with/without methanol) or THF (with/without methanol) solutions containing 5 nM sulforhodamine B (SRB) between two glass substrates. The PEO microdomains are aligned in the solution flow direction during the film preparation. The diffusional motions of individual SRB molecules are measured at different drying times to assess the microdomain radius and permeability. These parameters, on average, gradually decrease with an increase in drying time; however the trend differs slightly from one solvent system to another. A sharp decrease of microdomain radius is observed for benzene, benzene-methanol, THF and THF-methanol swollen films at initial drying condition (for example 2 days). In contrast, microdomain permeability does not decrease sharply; instead a gradual decreasing trend is seen for all solvent systems. In addition, mixing of a small amount of methanol (14% in PEO microdomains) either with benzene or with THF does not produce noticeable difference in the swelling of PEO microdoamins. Importantly, both benzene and THF offer similar microdomain swelling behavior at the same drying temperature, which is evident from the microdomain radius values, however THF shows comparatively larger microdomain permeability and better correlation between permeability and microdomain radius compared with benzene.
Keywords: Diblock copolymers; Polyclyrene; Polyethylene oxide; Single-molecule tracking